A PARSER CLASS IN JAVA TO EVALUATE ALGEBRAIC EXPRESSIONS - Ruiz Lizama, Edgar (2006)
The article presents a Parser class in Java to evaluate algebraic expressions using fundamental algorithms for the construction of compilers, passing from the conversion of expressions from infix to postfix, the evaluation of postfix expressions, the evaluation for precedence of operators, parser algorithms of precedence and construction algorithm of precedence functions. The goal of the article is to write a lexical analyser in a conventional language of systems programming, using the possibilities of input and output of Java language in order to read expressions to evaluate from the input, to process them and to send the results to the output.